The Influence of Work Motivation, Work Environment And Work Discipline on Employee Performance in The Personnel And Human Resources Development Agency (BKPSDM) of Malang City - Florianus Marto; Retno Ayu Dewi Novita; Yuni Setyawati (International Journal of Management and Business, 2026)
The aim of this study is to determine the effect of work motivation, work environment and work discipline on employee performance in the Malang City Human Resources and Human Resources Development Agency (BKPSDM), both partially and simultaneously. Types of Quantitative Research. The population of this study is that all employees at BKPSDM Malang City were 44 people, and the technique of determining the sample using total sampling. Instrument using a questionnaire. Data analysis using multiple linear regression. Hypothesis testing using the t test (partial) and F test (simultaneous). The results of multiple linear regression obtained by the three independent variables have a positive regression coefficient value, and the coefficient of Determination of R Square (R2) is 0.784 (contribution of the independent variable to the dependent variable of 78.4%). The results of testing the t test (partial) hypothesis found that the three independent variables have a tcount > ttable value significantly < 0.05 and the results of the F (simultaneous) hypothesis testing obtained the Fcount > Ftable with a significant value < 0.05. So it was concluded that work motivation, work environment and work discipline had a significant effect on employee performance in the Personnel and Human Resources Development Agency of Malang City, both partially and simultaneously. It is recommended to the Head of the Personnel and Human Resources Development Agency Malang City of Malang City to integrate efforts to increase work motivation, the creation of a conducive work environment, and uphold holistic work discipline in employee management policies to encourage overall performance improvement.